A Comparative Study of the Prevalence and Intensity of Borderline Personality Features in Male and Female High School Students in Fars Province - Seyede Fateme Sajadi; Habibe Riyahi; Zahra Sahraeeyan; Raziye Sadeghi; Fakhri Tajikzadeh; Tayebe Mahmoudi; Yadolla Zargar (Shiraz University of Medical Sciences, 2015)
Background: Borderline Personality Disorder (BPD) is the most important and prevalent entity, with a population prevalence rate of 1.4 to 5.9. Objectives: Although, the epidemiology of BPD is insufficiently known, our objective was to compare the cross-sectional prevalence and intensity of this disorder among high school male and female students. Patients and Methods: The study comprised of 1265 male/female high school students in educational year 2013 to 2014 in Fars province, selected by multi-stage random sampling. Data collection was done using Borderline Personality Features Scale-Children. The descriptive statistics, Chi-square test, student's independent t-test, and multivariate analysis of variance were used for data analysis. Results: The prevalence rate of borderline personality features in whole sample is 26.6%, with 34.2% in females and 17.4% in males There was a significant difference between males and females (P < 0.001, χ2 = 6.72). Regarding total scores and related four subscales, significant differences were found between the prevalence of borderline personality features in males and females; self-harm and negative relationship subscales were higher in male students. Conclusions: The results showed that there was a considerable gap between the real prevalence of borderline personality disorder in the general population and its prevalence in clinical records. Also, the prevalence of borderline personality disorder in non-clinical adolescent's population is higher than its prevalence in adult population. It shows the necessity for more specific investigations and designing predictive plans.